Quantitative Ultrasound Texture Feature Changes With Conservative Treatment of the Trapezius Muscle in Female Patients With Myofascial Pain Syndrome - (:unkn) unknown (NLM (Medline), 2021)
OBJECTIVE: We set out to assess whether quantitative ultrasound could be used to assess changes that occur after physical therapy in patients experiencing myofascial pain syndrome. METHODS: We consecutively recruited female subjects experiencing myofascial pain syndrome of the neck and shoulder region and provided 10 sessions of conservative physical therapy. A control group was recruited for textural analyses. We measured change in pain ratings, range of motion, and ultrasound texture features before and after the intervention and after 3 mos. RESULTS: We recruited 63 female myofascial pain syndrome subjects and 20 healthy controls. After treatment, the mean blob size (an ultrasound texture feature) value for each subject decreased from 30.84 ± 5.00 to 25.86 ± 5.67 on the right and decreased from 31.70 ± 5.51 to 28.08 ± 5.53 on the left (P < 0.0005). The blob count showed a significant increase only on the left side (P < 0.01). Corresponding to this were reductions in pain and disability scores after treatment and at 3 mos compared with retreatment (P < 0.0005 for all checkpoints). Cervical range of motion values were significantly increased only at 3 mos compared with pretreatment except for mean flexion range of motion. CONCLUSIONS: Ultrasound texture feature of blob size and count changes correspond to routine clinical outcomes after conservative physical therapy of myofascial pain syndrome in female individuals. Copyright © 2021 Wolters Kluwer Health, Inc. All rights reserved.